Comparaciones múltiples no paramétricas en la evaluación sensorial de la apariencia y sabor de tres marcas de cerveza comercial - Minchón y Cols., Carlos (2019)
The sensory evaluation of food is an important tool in the food industry. Sensory evaluation techniques applied to cheeses, cured meats, honey, water, olive oil and wine, can also be used in potential consumers tasting process to determine the perception of the organoleptic characteristics in elaboration of products and commercial products, generating the need to spread the application of nonparametric statistical methods. The purpose of this study is to determine the commercial beer brand with better appearance and flavor using nonparametric multiple comparisons. Trujillo Pilsen, Cristal and Brahma, brands with important acceptance in Trujillo market, were evaluated in appearance and flavor sensory for 60 potential customers using a 5-point hedonic scale. Was applied the Friedman test and multiple comparison tests and tests with a control, the control was Pilsen Trujillo beer. The data were processed by IBM SPSS 19 and Excel. Friedman test showed difference both in appearance (p = 0.000 <0.01) and flavor (p = 0.000 <0.01) between brands, Pilsen Trujillo in appearance and Cristal in flavor. Multiple comparison tests showed similarities between Cristal and Trujillo Pilsen beers in appearance (p> 0.05) and with Brahma beer in flavor (p> 0.05), both inferiors to Cristal in flavor. Was conclude that Cristal beer is the best in flavor and similar in appearance with Pilsen Trujillo, but higher than Brahma in both attributes. Furthermore, the ease application of nonparametric methods for multiple comparisons by ranks, let us to extend its use in sensory evaluation in elaboration of products and commercial products.